UK Built Environment postgraduate programme provision: sectoral context, viability and educational implications - Alan M. Forster; Laurent Galbrun; Nick Pilcher; Stuart Tennant; Nigel Craig; Mike Murray (Cogent Education)
Postgraduate (PG) Built Environment education provides higher level skills, yet, concerns of losing such provision exist, as UK universities are experiencing financial challenges from systemic governmental underfunding. This article presents survey findings evaluating three areas in PG Built Environment provision: (i) Institutional context and programmes offerings; (ii) Programme viability and institutional decision making; and (iii) Implications of change in programme offerings. Collectively, these support an understanding of ‘What is offered?’ ‘What is viable?’ and ‘What is the result of change in provision?’ Participants included Senior academics from a range of UK universities and disciplines. Results suggest more PG programmes are being opened (72%) than closed (35%), reflecting institutional aspirations to grow numbers via new offerings. No consensus exists regarding numbers for financial viability, although 10 to 30 students was commonly noted. Decisions to open and close programmes are largely ‘top-down’, from University Executive or Head of School, whilst arguments for retaining programmes with low student numbers typically come from staff at programme level. Regarding implications of change, policy makers are encouraged to engage with universities, employers and professional bodies, as findings point towards more online PG degrees, Continuing Professional Development activities and inhouse specialist training.